A SYSTEMATIC ANALYSIS OF THE IMPACT OF THE TEACHER PROFESSIONAL EDUCATION PROGRAM ON TEACHER PROFESSIONALISM IN TEACHING AND LEARNING ACTIVITIES IN INDONESIA - Wahyudin; Aripin, Syamsul (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
This study aims to systematically analyze the impact of the Teacher Professional Education (PPG) program on the improvement of teacher professionalism in teaching and learning activities in Indonesia. Teacher professionalism encompasses pedagogical, professional, social, and personal competencies, which are key indicators of educational quality. This research employs a Systematic Literature Review (SLR), reviewing three scientific articles published between 2022 and 2023 that are relevant to the topic. The findings indicate that the PPG program has a positive impact on enhancing teacher competencies, particularly in curriculum mastery, innovative teaching strategies, and work ethics. However, its effectiveness is still influenced by implementation quality, institutional readiness, and participant motivation. The study recommends ongoing evaluation and stronger integration between PPG training and actual classroom practices. These findings offer valuable insights for shaping national policies aimed at improving teacher quality and the effectiveness of the PPG program. Penelitian ini bertujuan untuk menganalisis secara sistematis pengaruh program Pendidikan Profesi Guru (PPG) terhadap peningkatan profesionalitas guru dalam kegiatan belajar mengajar di Indonesia. Profesionalitas guru mencakup kompetensi pedagogik, profesional, sosial, dan kepribadian yang menjadi indikator utama kualitas pendidikan. Penelitian ini menggunakan metode Systematic Literature Review (SLR), berdasarkan telaah terhadap tiga artikel ilmiah yang dipublikasikan dalam rentang tahun 2022–2023 dan relevan dengan topik. Hasil kajian menunjukkan bahwa program PPG memberikan kontribusi positif terhadap peningkatan kompetensi guru, khususnya dalam penguasaan kurikulum, strategi pembelajaran inovatif, dan peningkatan etos kerja. Namun demikian, efektivitas PPG masih dipengaruhi oleh kualitas pelaksanaan, kesiapan institusi penyelenggara, serta motivasi peserta. Penelitian ini merekomendasikan perlunya evaluasi berkelanjutan dan penguatan integrasi antara pelatihan PPG dengan praktik nyata di kelas. Temuan ini memberikan kontribusi penting dalam merumuskan kebijakan peningkatan mutu guru dan efektivitas program PPG secara nasional.